Antenatal diagnosis of achondroplasia - Dhungel, K; Gupta, MK; Ahmad, K; Ansari, S; Rauniyar, RK (Bangladesh Journal of Medical Science, 2013)
We report a interesting case of antenatal diagnosis of achondrpoplasia in a young multigravida who presented with term pregnancy for routine ultrasound assessment which revealed a single, live intrauterine fetus with a discrepancy between femur length (FL) and biparietal diameter (BPD), narrowing of the interpeduncular distance. The diagnosis of achondroplasia was made with a sonological skeletal survey and findings were correlated with radiological skeletal survey after the baby was delivered. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17443 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 84-87